Flow control in s-shaped aggressive diffuser using grooves on the inner and outer surfaces - Jessam, R.A. (Asian Research Publishing Network, 2016)
This paper presents CFD simulation results for S-shaped aggressive diffuser to establish grooves effectiveness in improving the flow patterns. Grooves have been proposed perpendicular to the flow direction in different planes along the aggressive diffuser. The simulated flow field was generated within a normal S-shaped diffuser with curvature of 45°/45°, and then simulated for aggressive diffuser with 30730° by reducing the total length by 22. CFD simulation was performed, under 3D assumption, on both normal and aggressive diffusers, as well as with and without grooves, through ANSYS-FLUENT 16.2 software. The renormalized group k-e model was used to simulate the turbulence. The simulation results were validated and were consistent with the findings of previous experimental and numerical studies. Results obtained in the current study indicated that the combination of grooves could effectively control the flow distortion in S-shaped aggressive diffusers. Predicted performance parameters, such as the coefficients of static pressure recovery and total pressure loss, suggested that the performance of the grooves was able to enhance the pressure recovery by 18.2 and total loss coefficient was reduced by 5.75 in comparison with the case of aggressive diffuser without grooves. ©2006-2016 Asian Research Publishing Network (ARPN).